Participatory action research on adaptive collaborative management of community forests: a multi-country model - McDougall, C.; Prabhu, Ravi; Kusumanto, Y. (Routledge, 2003)
This case study summary highlights CIFOR and partners’ participatory action research based project entitled ‘Adaptive and Collaborative Management of Community Forests’. The project, which included activities in Asia, Africa and Latin America, explored the potential contribution of collaboration and social learning based forest management to enhancing human and forest ecosystem well-being. The project combined participatory action research with more traditional social and biophysical research to create a valuable multi-country comparison that also had positive local impacts.